ASSESSMENT OF THE EFFECT OF ORAL HYGIENE ON THE COURSE OF INFLAMMATION IN GENERALIZED PERIODONTITIS - Moshel, Tetiana; Zaitsev, Andriy; Kotelevska, Natalia; Boychenko, Olga; Ivanytskyi, Igor (Eastern Ukrainian Medical Journal, 2024)
Introduction. The modern paradigm considers inflammatory and inflammatory-dystrophic periodontal diseases not only as a local inflammation of the periodontal tissues, which is caused by the microflora of oral biofilm, but also as a reaction of the whole body to the action of a bacterial infection. Knowledge about the relationship between the organism and the microflora of the oral cavity obtained using an index assessment can improve methods of prevention and treatment of inflammatory and inflammatory-dystrophic periodontal diseases. Therefore, the aim of the work was a mathematical analysis of the influence of oral hygiene on the course of gingival inflammation in generalized periodontitis. Methods. To achieve the goal, we assessed the dental status of 36 patients with stage I–II chronic generalized periodontitis (GP) against the background of the combined course of chronic cholecystitis (XX) and pancreatitis (CP) aged 17 to 64 years, who were being treated in the regional gastroenterological center of Poltava. Examination of patients with generalized periodontitis included generally accepted clinical methods. Objective criteria were used to study the periodontal status: the Schiller-Pysarev test, the PMA index according to Parma (1960), the periodontal index according to Russel (1956), the vacuum test of V.I. Kulazhenka (1960), thermometry of gingival papillae, ortho-pantomography of jaws. The state of oral hygiene was assessed using the Green-Vermillion index (1964). The diagnosis was made according to the classification of periodontal diseases by M.F. Danylevsky (1994). Statistical processing of the index assessment was carried out on a computer using the Microsoft Excel Office 2007 program. The reliability of the obtained results was analyzed according to the Student’s test. Mathematical analysis was carried out using online calculators and the computer program Excel 2010. The data in the groups had a normal distribution. Results. With the help of online calculators for calculating geometric indicators, the angles between the found functions and the tangents of these angles were calculated. In our case, it could be used as an indicator to calculate the ratio of the functions of the OHI-S index and the PMA index. The obtained equations were equations of the first degree, that is, linear equations – equations of a straight line. This indicated that there was a linear relationship between the metrics that related to their function. That is, the parameters of inflammation depended on the conditions that changed in the oral microbiome in the form of a linear combination. Graphs obtained during preprocessing and immediately after processing had a negative slope. This indicated that the lines would point downwards and the functions these lines represented would also decrease. It means that during the treatment, the intensity of inflammation of the gums would decrease, and the state of the periodontal tissues would correspond to the state of "improvement". Graphs obtained immediately after treatment and 6 months after treatment had a positive slope. This indicated that the directions of the lines would increase, as well as the functions that these lines represented. That is, after treatment, inflammation of the gums in conditions of insufficient oral hygiene would intensify again, which was confirmed by the PMA index. Conclusions. The analysis of numerical indicators of the ratio of the patient’s body to the microbiota of the oral cavity can be used to predict the course and consequences of the disease, as well as to adjust the treatment. The study of the relationship between microbiocenoses and their carriers with the involvement of mathematical methods that take into account the definition of the functional component between them will allow scientists and doctors to determine the integral component of the body’s reactions in response to a change in the state of microbiocenoses under the conditions of medical interventions.